Bloom-ism Perspective in Remote Learning during COVID-19 Outbreak in Indonesian EFL Context - Dewi, Kartika Sari; Livy, Sharyn (Universitas Muhammadiyah Jember, 2023)
From 2020 to early 2022, most education systems globally were required to be directed remotely due to the coronavirus disease (COVID-19) pandemic. This global phenomenon also forced the Indonesian government to take action by closing all schools and reorganizing the curriculum: the basic competencies taught were reduced but still emphasized higher-order thinking skills. In response to the sudden policy adjustment, teachers are challenged to design innovative and creative teaching and learning activities that could be conducted remotely. While many available studies have conceptualized Bloom’s theory from traditional classroom teaching, this study attempts to draw Bloom’s frameworks during the unusual online teaching because of the Covid-19 pandemic. The objective of the study is to investigate how two Indonesian English teachers reported their experiences with applying Bloom’s Digital Taxonomy (BDT) while teaching remotely. The research design was a qualitative case study. Data were collected using semi-structured interviews and analyzed using thematic analyses. BDT was used as the theoretical framework. The findings show that teachers emphasized more on the task-based language teaching method more than lecturing via Zoom. Teacher-centered learning activities were identified in the LOTS (lower-order thinking skills) stages, while student-centered learning activities were reflected during the HOTS (higher-order thinking skills) stages.